PENGARUH GEL NANOTRANSFERSOME EKSTRAK KULIT JERUK NIPIS (Citrus aurantifolia Swingle) TERHADAP EKSPRESI MMP-9 PADA PENYEMBUHAN LUKA ULKUS TIKUS WISTAR - Nenny Prasetyaningrum; Annisa Pramuditha Ardana (E-Prodenta Journal of Dentistry, 2023)
Background: Traumatic ulcers are generally caused by physical, chemical, or thermal trauma. When an ulcer occurs, wound healing processes such as hemostasis, inflammation, proliferation, and remodeling occur. In the wound healing process, the expression level of matrix metalloproteinase-9 (MMP-9) must be tightly controlled because increased expression of MMP-9 can delay wound healing by degrading the extracellular matrix (ECM) and collagen uncontrollably. Nanotransfersome gel of lime peel extract (Citrus aurantifolia Swingle) contains flavonoids, tannins, saponins, and alkaloids which have anti-inflammatory properties and can accelerate the wound healing process. Nanotransfersomes can improve tissue localization and minimize excessive drug release. Purpose: This study aims to determine the effect of lime peel extract nanotransfersome gel on the expression of MMP-9 on wound healing of wistar rats ulcers. Methods: This study used 4 groups of wistar rats with time series on days 3 and 7, namely the control group, the treatment group given lime peel extract, the treatment group given lime peel extract nanotransfersome gel, and the treatment group given standardized herbal medicine. Observation of the MMP-9 using 400x magnification. Result: Data analysis using One Way Anova test showed that there were significant differences in MMP-9 expression in the treatment groups K7 with P7B and P7A with P7B. Conclusion: Based on the results of the study it can be concluded that lime extract nanotransfersome gel can reduce MMP-9 expression in wound healing of wistar rats ulcers.   Keywords: wound healing, ulcers, nanotransfersome gel of lime peel extract, matrix metalloproteina